Effect of Freezing on the Shelf Life of Salmon - Paul Dawson; Wesam Al-Jeddawi; Nanne Remington (International Journal of Food Science)
Food shelf-life extension is important not only to food manufacturers, but also to home refrigeration/freezing appliance companies, whose products affect food quality and food waste. While freezing and refrigerating both extend the shelf life of foods, food quality deterioration continues regardless of the preservation method. This review article discusses the global fish market, the composition of fish meat, and the effects of freezing and thawing on salmon quality.